Collagen extraction from rainbow (Oncorhynchus mykiss) trout heads and skins - Duman, Muhsine (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Fish processing produces significant amounts of by-products. The disposal of these wastes can lead to environmental and human health problems; however, these by-products can often be transformed into high-value and beneficial products. This study investigated the physicochemical properties of gelatin extracted from the heads and skins of rainbow trout (Oncorhynchus mykiss). The yield of gelatin obtained from the heads and skins were 6.17 and 8.46%, respectively. The protein content of gelatin obtained from the skin (84.68%) was greater than that obtained from the head (81.9%) (P<0.05). Both gelatins exhibited slightly acidic pH values (6.42 for heads and 6.20 for skins). FTIR analysis confirmed typical collagen-specific spectral features in both samples. The gelatin obtained from the skin exhibited a lighter and more reddish-yellow color compared to the gelatin obtained from the head (P<0.05). The sensory analysis results indicated that both gelatin samples had a mild odor; however, the gelatin obtained from the head exhibited a easily more perceptible odor compared to that extracted from the skin (P<0.05). These findings suggest that the heads and skins of rainbow trout are appropriate sources for gelatin production and support the sustainable use of wastes from fish processing.
Extracción de colágeno de cabezas y pieles de trucha arcoíris (Oncorhynchus mykiss)
Keywords: Gelatin; trout by-products; physicochemical properties; FTIR analysis; sustainability